EVALUASI PELAKSANAAN PRAKTEK BENGKEL JURUSAN BANGUNAN DI KELAS XI SMK N2 KOTA SOLOK PROVINSI SUMATERA BARAT - 170-175 . Muhammad Gadapi (Universitas Negeri Padang, 2013)
The purpose of this research is to reveal whether practices implementation in workshop of SMKN 2 Solok had been well-implemented, in consideration of teachers, students, workshop’s preparations, workshop’s practices, tools and infrastructures. The type of this research is descriptive-quantitative. Population in this research is all students of XI TKK in SMKN 2 Solok which is amounted to 120 students and samples are XI class’s students amounted to 55 students. Data collection technique is questionnaire by using Likert scale. Data analysis technique is using percentage formulation. Results in this research show that tools and infrastructures in SMKN 2 Solok are well-equipped. Evaluation in SMKN 2 Solok had been implemented properly. Practices in this school are in conformity with schedules which had been planned by school practice’s implementer, and connected with teacher’s monitoring and involvement in practical implementation. Key words : -